Case Report: It's not always about the veins; intervention of bilateral May–Thurner Syndrome secondary to iliac aneurysm - Haq, Syed H.; Shah, Sidra R.; Chandra, Jaya; Kannan, Pavithra; Patel, Sandeep M. (Frontiers in Cardiovascular Medicine, 2023)
May–Thurner Syndrome (MTS) remains evasive because of the insidiousness and variable etiologies by which it can manifest. In this study, we examine a unique presentation of MTS resulting from compression of both common iliac veins by a right common iliac artery aneurysm that required complex endovascular venous and arterial intervention.